Concentrations and regularities of disperse-phase distribution of organochlorine pesticides, polychlorinated biphenyls and polycyclic aromatic hydrocarbons in natural water - Milyukin, Myhaylo; Gorban, Maksym (My University, 2021)
This article presents the monitoring results of organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs), and polycyclic aromatic hydrocarbons (PAHs) in surface water of the Dnieper River for the period 2011–2019. Total levels of OCPs, PCBs and PAHs consist of 1,4–17,1; 2,8–57,2; and 7,5–378,6 ng/L, respectively. A significant increase in pollution levels was not identified. Research results of the disperse-phase distribution of these substances in water were also provided. Less than half of the total contents of pollutants were in the water phase. Average water-soluble parts of OCPs, PCBs, and PAHs accounted for 32, 42, and 44 %, respectively. It was shown that water-soluble parts of individual pollutants decrease with the increase in the coefficients of hydrophobicity of compounds. The clearest reliable, relevant correlation between water-soluble parts of individual congeners and coefficients of hydrophobicity was obtained for PCBs.
Keywords: OCPs; PCBs; PAHs; surface water; the Dnieper River; monitoring; SPM; coefficient of hydrophobicity; поверхневі води; річка Дніпро; моніторинг; коефіцієнт гідрофобність; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів